The Art of Disruptive Politics:The relationship between Dadaists' use of creative iconoclasm and climate activists' use of art vandalism - Vorster, Nicola (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.